Marketing Communication Strategy of Certified Superior Seeds in the Oil Palm Seed Enlargement Industry (Elaeis guineensis) in CV. Tenera of Penajam Paser Utara Regency - Moh Nasir Abd Majid; Syamsu Rizal; Mujahid (Universitas Muhammadiyah Palu, 2024)
This study aims to find out and analyze the marketing communication strategy of Certified superior seed CV. Tenera in the Oil Palm Seed Enlargement Industry (Elaeis guineensis) in Penajam Paser Utara Regency. The research method used is qualitative descriptive with data collection through in-depth interviews, observations, and document studies. Data analysis using content analysis. The results showed that out of eight marketing communication strategies, only two were implemented by CV. Tenera, which is direct marketing and word-of-mouth marketing. Meanwhile, advertising, personal selling, public relations and publicity have not been implemented The main inhibiting factors that affect the implementation of all strategies are limited advertising and promotion, limited personal selling and limited public relations, this is due to the pattern of planning and execution in marketing communication strategy CV. Tenera uses a top down marketing communication strategy. All control lies with the president director, Mr. Adi Paimanais. On the other hand, there are supporting factors that contribute to the success of CV. Tenera marketing communication strategies. Among others, budget availability, consumer readiness to buy products, the existence of competitors and media availability preferences. In addition, CV. Tenera is committed to providing a guarantee until harvest in addition to certified superior seeds. This research provides recommendations for CV Tenera Companies. to consider developing a more holistic and optimal marketing communication strategy in overcoming obstacles and utilizing the advantages of supporting factors that already exists.